2010
DOI: 10.1016/j.jpeds.2009.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorders in Extremely Preterm Children

Abstract: Objectives To investigate the prevalence, correlates, and antecedents of autism spectrum disorders (ASD) in extremely preterm children. Study designWe conducted a prospective study of all births <26 weeks gestation in the United Kingdom and Ireland in 1995. Of 307 survivors at 11 years, 219 (71%) were assessed and compared with 153 term-born classmates. Parents completed the Social Communication Questionnaire (SCQ) to assess autism spectrum symptoms, and ASD were diagnosed by using a psychiatric evaluation. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
220
5
12

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(259 citation statements)
references
References 34 publications
22
220
5
12
Order By: Relevance
“…In a recent whole-population study, we reported that 8% of 219 children born at not more than 25 completed weeks of gestation met the diagnostic criteria for ASD in middle childhood. 1,2 This is markedly higher than the 0.2 to 0.7% prevalence reported in the general population. 3,4 As early diagnosis and behavioural intervention for ASD significantly improves outcome, 5,6 screening may be particularly important in high-risk groups such as extremely preterm children.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…In a recent whole-population study, we reported that 8% of 219 children born at not more than 25 completed weeks of gestation met the diagnostic criteria for ASD in middle childhood. 1,2 This is markedly higher than the 0.2 to 0.7% prevalence reported in the general population. 3,4 As early diagnosis and behavioural intervention for ASD significantly improves outcome, 5,6 screening may be particularly important in high-risk groups such as extremely preterm children.…”
mentioning
confidence: 63%
“…Furthermore, children with ASDs in the general population are significantly more likely to have increased cerebral volumes, independent of non-verbal IQ, 17 whereas ASD symptoms have been associated with smaller head circumferences in extremely preterm children. 1 Temporal periventricular leukomalacia in extremely preterm children has been linked to abnormal visual processing of bodily motion -a process thought to be deficient in individuals with difficulties in social interaction. 18 It has, therefore, been suggested that the associates and risk factors for a diagnosis of ASD are indicative of a different aetiological mechanism for autism in extremely preterm children than in the general population, and one that is associated with altered brain development.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the same analysis on one additional gene named oxytocin receptor (OXTR) whose mRNA and protein expression has been shown to be markedly upregulated in association with labor in primary human amnion epithelial cells [18]. studies have demonstrated that the methylation status of the promoter region of this gene is associated with tissue-speci�c OXTR expression [28] and the development of autism [19], a disorder linked to PTB [20,21,33,34]. ese �ndings intrigued us to investigate whether DNA methylation could represent one mechanism regulating the labor-associated activity of OXTR in the amnion.…”
Section: Bi��l�t� S����n�in� �Bs� Anal��i� Of Di��r�ntial M�th�la-tionmentioning
confidence: 99%
“…This less optimal development shows deficit persistence up to childhood (Rose, Feldman, & Jankowski, 2009), and early attention processes in preterm infants are related to parent-reported symptoms of attention deficit hyperactivity disorder later in life (Lawson & Ruff, 2004), which is diagnosed in a higher proportion of children born preterm compared to full term (Johnson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%